Acceptance and commitment therapy on perceived stress and psychological flexibility of psychiatric nurses: a randomized control trial - Seyyed Arman Hosseini Zarvijani; Ladan Fattah moghaddam; Samaneh Parchebafieh (BMC, 2021)
Abstract Background Nursing in psychiatric wards is considered a highly stressful career due to the type of patients and the problem of communicating with them. Finding appropriate solutions to overcome this stress can improve the general health of nurses and improve their quality of work. The aim was to investigate the impact of Acceptance and Commitment Therapy (ACT) on the perceived stress (PS) and psychological flexibility (PF) of nurses in psychiatric wards. Methods A total of 70 nurses of Razi Psychiatric Center of Tehran were randomly selected and divided into two experimental and control groups of 35. In addition to routine interventions, the experimental group was provided with eight 2-h sessions of ACT training, whereas the control group only received routine interventions. Prior to the intervention sessions and a month after the last session, demographic information, PS scale, and Acceptance and Action Questionnaire (2nd Edition) were completed in both groups. Results There was a significant difference regarding the PS level (P = 0.002) and PF (P = 0.001) in the control and experimental groups; the experimental group showed lower PS and higher PF. Conclusions ACT can lead to reduced PS and improved PF, which can be considered as a solution to empower nurses working in psychiatric wards. Trial registration This was registered in Iranian Registry of Clinical Trials (IRCT) (clinical trial code: IRCT20180506039557N1 . Registered 2018-10-31. Retrospectively registered, https://en.irct.ir/trial/31040